2011
DOI: 10.1007/s00234-011-0868-9
|View full text |Cite
|
Sign up to set email alerts
|

CT angiography helps to differentiate acute from chronic carotid occlusion: the “carotid ring sign”

Abstract: The carotid ring sign helps to differentiate acute from chronic carotid occlusion. If further confirmed, this information may be helpful in studying ischemic symptoms and selecting treatment strategies in patients with carotid occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A previous study, based on circumstantial clinical and radiological imaging data, defined chronic occlusion as occlusion lasting more than 4 weeks ( 5 ). Chronic occlusion may be distinguished from acute occlusion by computed tomography (CT) angiography (CTA), as the ‘carotid ring sign’ (defined as the presence of hypodensity in the ICA and/or contrast within the carotid wall) is visible in CTA of acute ICA occlusion ( 4 ). Another study suggested, according to current data in the field of cardiovascular medicine, that the minimum threshold for chronic total occlusion (CTO) of the ICA should be at least 3 months, and possibly even more than six months ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study, based on circumstantial clinical and radiological imaging data, defined chronic occlusion as occlusion lasting more than 4 weeks ( 5 ). Chronic occlusion may be distinguished from acute occlusion by computed tomography (CT) angiography (CTA), as the ‘carotid ring sign’ (defined as the presence of hypodensity in the ICA and/or contrast within the carotid wall) is visible in CTA of acute ICA occlusion ( 4 ). Another study suggested, according to current data in the field of cardiovascular medicine, that the minimum threshold for chronic total occlusion (CTO) of the ICA should be at least 3 months, and possibly even more than six months ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 11 – 13 Some studies confirmed the moderate or strong agreement between the neurologist and radiologist in case of proximal or distal occlusion of ICA or in case of CTA perfusion evaluation. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“… 8 Therefore, in our study we intended to assess the interrater agreement of the diagnosis of occlusion of intracranial arteries at CTA between a radiologist, a general neurologist and a neurologist-stroke specialist. Some previous studies confirmed the moderate or strong agreement between a neurologist and a radiologist in case of proximal or distal occlusion of the internal carotid artery (ICA) or in case of CTA perfusion evaluation, 9 , 10 but the agreement has not been tested in the case of CTA which was performed before recanalization therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Perfusion or rather postcontrast imaging since dynamic imaging at the moment would provide a too low resolution is possible also with CT and MR. One example where enhanced imaging has been of help is the so-called carotid ring sign that helps to differentiate acute from chronic occlusions. 45 From a radiological point of view, the degree of stenosis from which treatment will be decided is usually done by using the NASCET or ECST criteria, with measurements done on the images in a sagittal projection. While this applies to plaque measurements, further criteria for the evaluation before treatment may be taken into account such as plaque progression (following stenosis degree on multiple followup examinations) or also by looking at plaque morphology.…”
Section: Extracranial Carotid Artery Diseasementioning
confidence: 99%